2014
DOI: 10.1155/2014/591867
|View full text |Cite
|
Sign up to set email alerts
|

Current Approaches for Predicting a Lack of Response to Anti-EGFR Therapy inKRASWild-Type Patients

Abstract: Targeting epidermal growth factor receptor (EGFR) has been one of the most effective colorectal cancer strategies. Anti-EGFR antibodies function by binding to the extracellular domain of EGFR, preventing its activation, and ultimately providing clinical benefit. KRAS mutations in codons 12 and 13 are recognized prognostic and predictive biomarkers that should be analyzed at the clinic prior to the administration of anti-EGFR therapy. However, still an important fraction of KRAS wild-type patients do not respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…58,59 Genotype is an important determinant of both the response to treatment and the susceptibility to adverse reactions for a wide range of drugs, 60,61 for example response to EGFR inhibitors has been shown to be dependent on gene expression in colon cancer, with studies demonstrating a treatment interaction between RAS status and the effectiveness of EGFR inhibitors. [62][63][64] In line with research evaluating the negative impact of RAS mutations on the effectiveness of EGFR inhibitors, approval for the use of anti-EGFR antibodies has now been limited to people with mCRC with RAS WT tumours. 44,65 Tumour samples from trial populations supporting the original licensed indications were evaluated retrospectively for RAS status.…”
Section: Methods For Reviewing Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…58,59 Genotype is an important determinant of both the response to treatment and the susceptibility to adverse reactions for a wide range of drugs, 60,61 for example response to EGFR inhibitors has been shown to be dependent on gene expression in colon cancer, with studies demonstrating a treatment interaction between RAS status and the effectiveness of EGFR inhibitors. [62][63][64] In line with research evaluating the negative impact of RAS mutations on the effectiveness of EGFR inhibitors, approval for the use of anti-EGFR antibodies has now been limited to people with mCRC with RAS WT tumours. 44,65 Tumour samples from trial populations supporting the original licensed indications were evaluated retrospectively for RAS status.…”
Section: Methods For Reviewing Effectivenessmentioning
confidence: 99%
“…60,61 In CRC response to EGFR inhibitors has been shown to be dependent on gene expression; studies have demonstrated a treatment interaction between RAS status and the effectiveness of EGFR inhibitors. [62][63][64] It was in line with these research developments evaluating the negative impact of RAS mutations on the effectiveness of EGFR inhibitors that tumour samples from trial populations supporting the original licensed indications were evaluated retrospectively for RAS status. Therefore, data are not from the ITT population for any of the included studies, but are from a subgroup of people contained within the original RCTs.…”
Section: Applicability To the Nhs In Englandmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent identification of molecular genetics has enabled considerable advancements in the management of patients with advanced CRC. The development of targeted therapies directed against specific mutations such as those in the epidermal growth factor receptor (EGFR) tyrosine kinase gene has improved treatment efficacy and clinical outcome in advanced CRC patients [ 1 4 ]. However, CRCs are molecularly heterogeneous tumors that harbor various gene alterations including mutations in KRAS , BRAF , and PIK3CA , as well as HER2 amplification; many patients with these mutations therefore experience resistance against anti-EGFR drugs and exhibit poor prognosis [ 2 , 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly Kras is a biomarker associated with decreased responses to anti-EGFR therapies and is theorised that Kras mutations independently activate the downstream pathways of EGFR including RAS/MAPK signalling (213). Kras mutation status and not EGFR expression dictates cetuximab use in metastatic colorectal cancer (213,214).…”
Section: Cscchn Overexpress Egfr Highlighting Its Potential Role In Pmentioning
confidence: 99%